The challenge of establishing world-class universities - Salmi, Jamil (Directions in development. Human development., 2009)
Governments are becoming increasingly aware of the important contribution that high performance universities make to competitiveness and economic growth. This book explores what are the challenges involved in setting up globally competitive universities, also called "elite", or "flagship" universities.